The age of obesity onset affects changes in subcutaneous adipose tissue macrophages and T cells after weight loss - Murphy, Jessica; Morais, José A.; Tsoukas, Michael A.; Cooke, Alexandra B.; Daskalopoulou, Stella S.; Santosa, Sylvia (Frontiers in Immunology, 2025)
IntroductionAdipose tissue inflammation, driven in part by immune cells, may contribute to the elevated type 2 diabetes risk in adults with childhood-onset obesity (CO) compared to those with adult-onset obesity (AO). Weight loss can modify adipose tissue immune cell composition, but whether these changes differ by obesity onset remains unknown.MethodsWe compared abdominal and femoral subcutaneous adipose tissue (SAT) immune cell percentages between people with CO and AO before and after moderate (~10%) weight loss. We collected abdominal and femoral SAT from females with CO or AO before (CO: n=14; AO: n=13) and after (CO: n=8; AO: n=6) diet- and exercise-induced weight loss. We used flow cytometry to quantify the percentages of macrophages and T cells in the stromovascular fraction of both SAT regions.ResultsAbdominal CD68+CD206- ‘pro-inflammatory’ macrophages were slightly higher in AO than CO at baseline but declined in AO only, equalizing between groups after weight loss. Femoral CD68+CD206- macrophages, as well as abdominal and femoral CD68+CD206+ ‘anti-inflammatory’ macrophages and CD3+CD8+ T cells, did not differ between groups at baseline or change after weight loss. Abdominal and femoral CD3+CD4+ T cells—potentially pro- or anti-inflammatory—increased after weight loss in AO but remained unchanged in CO.DiscussionOur findings, though preliminary, do not support the hypothesis that SAT immune cell profiles account for the elevated type 2 diabetes risk in CO. Weight loss appears to alter some immune cell populations in AO but not in CO. The long-term metabolic consequences of these changes—or lack thereof—remain to be determined.